INOVASI PENINGKATAN KOMPETENSI GURU MELALUI EDUKASI ASESMEN PEMBELAJARAN BERDIFERENSIASI PADA KURIKULUM MERDEKA DI SMP ISLAM TERPADU TAHFIDZUL QUR’AN MAJENE - M, Musdar; Junaedi, Ahmad (Jurnal Abdi Insani, 2025)
The Merdeka Curriculum is a curriculum that helps educators create quality learning according to the needs and environment of the students. A good educator is one who possesses professional competence, which can be achieved by conducting differentiated learning assessments according to the applicable curriculum. Since the Merdeka Curriculum was established as the National Curriculum, teachers are required to be able to carry out differentiated learning assessments. The aim of this activity is to enhance teachers' competence in creating differentiated learning assessments within the Merdeka Curriculum at SMP Islam Terpadu Tahfidzul Qur’an Majene. The method used includes material delivery and discussion, as well as training and integrated mentoring in workshop activities. This method is used so that after listening to the material and participating in discussions, each teacher is expected to be able to create and conduct differentiated learning assessments in each subject taught, according to the educational level, starting from the planning, implementation, and evaluation stages of the learning process. Results show an improvement in teacher competence through education on differentiated learning assessments within the Merdeka Curriculum at SMP Islam Terpadu Tahfidzul Qur’an Majene. Teacher competence before the differentiated learning assessment education activity was at an average value of 44.45%. Subsequently, data analysis of the improvement in teacher competence after the differentiated learning assessment education activity showed an average value of 75.25%. This data indicates an increase in teacher competence by 30.75% after the education activity.